The Fact of Technology In The Context Of Islamic Education - Sanzi, Velly; Sabana, Siti Zahra Walidatus; Pramudita, Suryaning Dyah; Ernawati, Lilis Endang (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Technological developments and advances have an impact on people's lives around the world, one of which is in the field of education. Technology used in education can maximize the teaching and learning process. However, the use of technology requires adjustment and readiness from educators and students. This study aims to examine problems related to the nature of technology in the context of Islamic education. The method in this study uses qualitative methods with a literature research approach where the author obtains and collects sources of information from previous researchers related to the researcher's topic then analyzes the data by collecting and understanding relevant reading sources then making the data in the form of research reports. The results of the study show that technology in the Islamic view can be utilized when it has been legalized by Islamic law. If it is forbidden by Islamic law, then a Muslim must follow the provisions of sharia by not using it. Islam does not hinder the progress of science and technology nor is it anti-technological products, the most important thing is that Muslims can avoid the negative effects of technology and can use technology in accordance with the provisions of the Qur'an and hadith, as well as in the use of technology in education an educator must pay attention to the guidance of sharia in using technology in the teaching and learning process.